Acetic Acid Promoted Direct Iodination of Terminal Alkynes with N-Iodosuccinimide: Efficient Preparation of 1-Iodoalkynes - Yao, Ming; Zhang, Jingjing; Yang, Sen; Liu, E; Xiong, Hangxing (Synlett, 2020)
An efficient and highly chemoselective approach for the direct iodination of terminal alkynes using acetic acid as N-iodosuccinimide activated reagent under metal-free conditions has been developed. This facile process tolerates a variety of terminal alkynes and provides the desired products in good to excellent yields (up to 99%).
Keywords: terminal alkynes; halogenation; 1-iodoalkynes; carboxylic acids; N-iodosuccinimide